Variasi Genetik Spesies Mangrove Ceriops tagal berdasarkan Marka RAPD - Dhuta Sukmarani (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2013)
Ceriops tagal are found at Segara Anakan Cilacap, Baluran National Park and Karimunjawa National Park. Information on the genetic diversity can be used for conservation policy. Genetic variation of C. tagal were analysed by using Random Amplified Polymorphic DNA (RAPD). This study aims to determine the genetic variation in each population and between populations C. tagal based on RAPD markers. The total DNA was extracted with CTAB extraction method. Amplification was performed using 10 primer (OPA-3, OPA-10, OPB-1, OPB-6, OPB-7, OPB-8, OPB-10, OPB-12, OPB-17 and OPB-18).  Amplification includes pradenaturation at 94°C for 5 min, followed by 45 cycles of denaturation at 94°C for 1 min, primer annealing at 37°C for 1 min, and primer elongation on 72°C for 1 min 30 sec, final extension at 72°C for 5 min and ends with holding at 4°C for 1 min. The analysis was done by changing the pattern of fragments to binary data (for bands appear = "1" and for bands do not appear = "0"). It is done using a program GenAlEx 2.1 and NTSYS-PC 6.1. A population that has the highest genetic variation (h) was Segara Anakan (0.308), followed by Baluran (0.295) and Karimunjawa (0.123). Baluran has the highest polymorphism (75.00%), Segara Anakan 69.23%, while Karimunjawa was 30.77%. The results of AMOVA, showed that the percentage of genetic variation within populations is greater (77%) than among populations (23%). The results of PCA analysis showed a similar pattern of genetic distance and UPGMA. Samples of Karimunjawa clustered with samples of the population, SA1 and SA3 likely close to the sample of Karimunjawa and SA2 are likely not one group with another sample of the Segara Anakan. Results of mantel test, the value of r = 0.347 and p = 0.02.